The Comparison Effect of the Positive Thinking Traning with and without Written Disclosure and Acceptance and Commitment Therapy on Perceived Stress in Women with Breast Cancer - Mojtaba Moeinvaziri; Parvin Ehteshamzadeh; Farah Naderi; Sahar Safarzadeh (Iranian Evolutionary Educational Psychology Journal, 2022)
The aim of this research was to study the comparison effect of the positive thinking training with and without written disclosure and acceptance and commitment therapy on perceived stress in women with breast cancer. This design of the study was pretest, posttest control group. The sample include 60 women with breast cancer (15 group experimental 1 (positive thinking training with written disclosure), 15 group experimental 2 (positive thinking training), 15 group experimental 3 (acceptance and commitment) and 15 group control) were randomly assigned.  The perceived stress Cohen et al. (1983) scale was used to collect data. For analyzing the results we used covariance (MANCOVA and ANCOVA) and Bonferroni test. The results indicated that positive thinking training with written disclosure; positive thinking training without written disclosure and ACT decreased the perceived stress in women with breast cancer in three experimental groups in comparison to the control group. According to results the positive thinking training with written disclosure was more effective compare to positive thinking training without written disclosure and ACT on the perceived stress in women with breast cancer.